Long Term Changes to the Positions and Heights of Sandwaves in the Southern North Sea - Wright, Peter (The International Hydrographic Review, 2018)
To keep British Admiralty charts safe for use for navigation, Hydrographer of the Navy resurveys the most critical areas of sandwaves on the UK continental shelf annually or every few years. Over the last 10 to 20 years, the UK Hydrographic Office has acquired large amounts of data for the areas that are most frequently resurveyed. This paper describes the findings of an examination of the surveys of one of these areas. The main aims of the paper are to provide the reader with an up-to-date assessment of the mobility of sandwaves in the southern North Sea, and to make available to others data on the movement of sandwaves.